2020
DOI: 10.1096/fj.201903183rrr
|View full text |Cite
|
Sign up to set email alerts
|

NPM1 mutant maintains ULK1 protein stability via TRAF6‐dependent ubiquitination to promote autophagic cell survival in leukemia

Abstract: Nucleophosmin (NPM1) mutations are the most frequent genetic alteration in acute myeloid leukemia (AML) and aberrant cytoplasm-dislocated NPM1 mutant is a distinct biological characterization of this disease. Our group previously reported that NPM1 mutant elevated autophagy activity and autophagy activation contributed to leukemic cell survival. However, the molecular mechanisms by which cytoplasmic NPM1 mutant involving in the autophagy pathway has not been fully elucidated.Here, we showed that Unc-51-like ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…GTPases RAB2 can also interact with the ULK1 complex, thereby promoting the recruitment of the ULK1 complex to form autophagosomes 189 . Interestingly, NPM1 mutant NPM1-mA could interact with ULK1 protein and positively regulate ULK1 protein levels and contribute to leukemic cell survival 190 . IRGM , encoded by a human gene for inflammatory disease risk, plays anti-inflammatory roles by promoting the interaction and co-assembly of ULK1 and Beclin 1 and the formation of the ULK1 complex 191 .…”
Section: The Molecular Basis Underlying the Regulation Mechanism Of Ulk1mentioning
confidence: 99%
“…GTPases RAB2 can also interact with the ULK1 complex, thereby promoting the recruitment of the ULK1 complex to form autophagosomes 189 . Interestingly, NPM1 mutant NPM1-mA could interact with ULK1 protein and positively regulate ULK1 protein levels and contribute to leukemic cell survival 190 . IRGM , encoded by a human gene for inflammatory disease risk, plays anti-inflammatory roles by promoting the interaction and co-assembly of ULK1 and Beclin 1 and the formation of the ULK1 complex 191 .…”
Section: The Molecular Basis Underlying the Regulation Mechanism Of Ulk1mentioning
confidence: 99%
“…Another group demonstrated that in NPM1-mutated AML, the glycolytic enzyme PKM2 (pyruvate kinase M2) activates autophagy by increasing the phosphorylation of key autophagy protein BECLIN1 and contributes to cell survival [ 36 ]. Finally, NPM1 mutant can also interact with ULK1, a core autophagy protein that promotes TRAF6-dependent ULK1 ubiquitination via miR-146, maintaining ULK1 stability and activity and promoting autophagic cell survival [ 38 ].…”
Section: Recurrent Genetic Aml Alterations Associated With Autophagymentioning
confidence: 99%
“…K63-linked ubiquitination mediated by the E3 ubiquitin ligase TRAF6 is a crucial posttranslational modification for ULK1 protein. Unlike K48 linkage, K63-linked ubiquitination has a positive effect on protein stability of ULK1 and its participation in autophagosome formation [ 63 ].…”
Section: Mirnas Are Involved In Autophagy Via Regulation Of E3 Ubiquitin Ligasesmentioning
confidence: 99%